Midcentury modern art in Texas - Edwards, Katie Robinson, 1964- (University of Texas, 2014)
Before Abstract Expressionism of New York City was canonized as American postwar modernism, the United States was filled with localized manifestations of modern art. One such place where considerable modernist activity occurred was Texas, where artists absorbed and interpreted the latest, most radical formal lessons from Mexico, the East Coast, and Europe, while still responding to the state?s dramatic history and geography. This barely known chapter in the story of American art is the focus of Midcentury Modern Art in Texas. Presenting new research and artwork that has never before been published, Katie Robinson Edwards examines the contributions of many modernist painters and sculptors in Texas, with an emphasis on the era?s most abstract and compelling artists. Edwards looks first at the Dallas Nine and the 1936 Texas Centennial, which offered local artists a chance to take stock of who they were and where they stood within the national artistic setting. She then traces the modernist impulse through various manifestations, including the foundations of early Texas modernism in Houston; early practitioners of abstraction and non-objectivity; the Fort Worth Circle; artists at the University of Texas at Austin; Houston artists in the 1950s; sculpture in and around an influential Fort Worth studio; and, to see how some Texas artists fared on a national scale, the Museum of Modern Art?s "Americans" exhibitions. The first full-length treatment of abstract art in Texas during this vital and canon-defining period, Midcentury Modern Art in Texas gives these artists their due place in American art, while also valuing the quality of Texan-ness that subtly undergirds much of their production.